(untitled) (Nonconventional Technologies Review, 2021)
In order to weld the copper pipe components of a heat exchanger assembly for a centrifugal air compressor CCAE 15-300, experiments were performed on a test piece. In order to establish the welding parameters, a test piece was manufactured, identical in terms of quality and dimensions, with the heat exchanger assembly. The aim of the paper is to develop a software program for an 8-axis robotic welding system, with CLOOS CST FLEX S laser sensor and WIG AC / DC GLW 500 welding source and to establish the optimal welding parameters. The robotic software system will be implemented in its control console having the objective to weld the test piece. Furthermore, the operating technique used to program the robotic system is presented so that it can weld the ends of the copper pipes to the heat exchanger assembly within the test piece used. After the welding of the test piece is performed, the analysis of macro and microscopy is presented on the paper and was performed using a piece cut on the direction of the holes adjacent to the pipe that was extracted from the test piece.